Real-world characteristics and treatment patterns in essential thrombocythemia: a population-based cross-sectional study in Taiwan between 2020 and 2021 - Ming-Sun Yu; Lennex Hsueh-Lin Yu; Shih-Hao Huang; Tsung-Hsien Tsai; Alex Jia-Hong Lin; Josef T. Prchal; Min-Chi Chen; Kuan-Der Lee (Therapeutic Advances in Hematology)
Background: Essential thrombocythemia (ET) is a Philadelphia chromosome-negative myeloproliferative neoplasm that is characterized by thrombocytosis and an elevated risk of thrombosis and hemorrhage. We aimed to ascertain the demographics, treatment patterns, and risk of recurrent thrombosis among patients with ET in Taiwan. Objectives: To investigate the patient characteristics, proportion of treatment, age-specific treatment pattern, average daily dose, and risk of recurrence of thrombosis in patients with ET. Design: A population-based cross-sectional study was conducted between January 1, 2020 and December 31, 2021. Methods: This study utilized data from the National Health Insurance Research Database in Taiwan. Patients with ET were identified based on ICD-10-CM codes, and their demographic, clinical, and treatment data were analyzed. Descriptive and statistical analyses were employed to compare patient characteristics, treatment modalities, and recurrence of thrombotic events. Results: Among the 4503 patients with ET (prevalence: 19.3 cases per 100,000 population), the mean age was 58.1 years, with a female predominance (60.3%). Thrombosis occurred in 3.8% of patients during the study period, with a recurrence rate of 30.5% in patients with a history of thrombosis. Hydroxyurea (46.8%) and anagrelide (30.2%) were the most common treatments, with younger patients receiving higher therapeutic doses. Despite cytoreductive therapy, younger patients demonstrated higher recurrence rates of thrombosis. The cumulative incidences of secondary myelofibrosis and acute myeloid leukemia were 2.6% and 0.6%, respectively, over 2 years. Conclusion: This study highlights the burden of ET in Taiwan and reveals significant unmet needs in thrombosis prevention, particularly among younger patients. Real-world treatment patterns diverge from recommendations in guidelines, and this finding emphasizes the need for individualized therapeutic strategies to optimize patient outcomes. Further research, such as a longitudinal study, is warranted to investigate the risk factors of thrombosis, disease progression, and mortality in this cohort.